New Oriental tribe Iscini, new non-dilatognathan species of Notophlebia Peters & Edmunds 1970 and independent origin of Dilatognathus-type mouth apparatus in Atalophlebiinae (Ephemeroptera: Leptophlebiidae) - Kluge, Nikita J. (Zootaxa, 2014)
A new tribe, Iscini tr. n., comprising the Oriental genera Isca Gillies 1951 and Notophlebia Peters & Edmunds 1970, is established. A new species, Notophlebia ganeshi sp. n., is described based on male and female imagos reared from larvae. The new species markedly differs from N. jobi Sivaramakrishnan & Peters 1984 by its non-specialized larval mouth apparatus. The larva of N. jobi has a highly specialized mouth apparatus of the «Dilatognathus-type»; this type of mouth apparatus has evolved independently in several non-related leptophlebiid taxa.